Preparation and Characterization of PVA/Na-CMC Hydrogel from OPEFB Cross-Linked by Maleic Anhydride - Triana Kusumaningsih; Abu Masykur; aulia Syifa Aninditha; Maryam Rahmi Utami (EduChemia (Jurnal Kimia dan Pendidikan), 2022)
PVA/Na-CMC hydrogels were prepared from polyvinyl alcohol (PVA) and Na-CMC isolated from OPEFB. Maleic anhydrous (MA) was introduced as a crosslinking agent during the formation of the hydrogel process. The characterization of the PVA/Na-CMC hydrogels was carried out using Fourier Transform Infrared (FTIR), Scanning Electron Microscope (SEM), and physical characterization methods, including swelling ratio and gel fraction analysis. The addition of MA was observed to increase the number of crosslinks. The optimum PVA/Na-CMC hydrogel composition was achieved at a PVA: Na-CMC ratio of 5:3 (P5C3M), with a pore size of approximately 3.643 ± 0,913 μm, a swelling ratio of 3104%, and a gel fraction value of 72.72%.